Evaluatıon of adverse events following immunization reported during national immunization programs (Between 2017-2019 in Ankara Province) - A. Çigdem Simsek; Elif Arabulan; Nilufer Tavukçu; Sertaç Çankaya; Belgin Gulhan; Aslinur Ozkaya-Parlakay (Taylor & Francis Group, 2021)
Vaccination services are important in primary health-care service. The Expanded Programme on Immunization (EPI) began in 1981 in Turkey. Vaccines are generally safe products; although rare, undesirable effects may be observed after vaccination. In order to increase vaccination rates, vaccine acceptability and service quality; the Vaccine Adverse Event Reporting System (VAERS) and performing necessary interventions are indispensable parts of vaccination programs. This study aimed to evaluate Adverse Events Following Immunization (AEFI) cases during 2017-2019 in Ankara. A total of ~1.7 million doses of vaccine were administered, and only 71 adverse events following immunization (AEFI) were reported (0.41 cases/million doses of risk). AEFI forms were examined, and of these 71 cases, 17 (24%) were hospitalized and 54 (76%) were followed-up.